2019
DOI: 10.1111/ced.14095
|View full text |Cite
|
Sign up to set email alerts
|

Melanoma‐associated retinopathy

Abstract: Summary Melanoma‐associated retinopathy (MAR) is a rare paraneoplastic autoimmune manifestation of cutaneous malignant melanoma. Patients classically present with acute onset night blindness, positive visual phenomena and visual field defects, and typically have significantly reduced quality of life as a result. Early recognition of MAR is of prognostic significance as it can precede the diagnosis of primary or metastatic malignant melanoma, and early treatment can lower the risk of irreversible immunological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 32 publications
0
14
0
6
Order By: Relevance
“…One patient with pre-existing glaucoma experienced ocular IrAE as the only IrAE, occurring after her first dose of pembrolizumab, and this led to treatment discontinuation. Four patients were diagnosed with anterior uveitis, one had intermediate uveitis, one had melanoma-associated retinopathy (MAR) 19,20 and one had suspected ocular ischaemic syndrome. 21 All patients had bilateral eye involvement.…”
Section: Resultsmentioning
confidence: 99%
“…One patient with pre-existing glaucoma experienced ocular IrAE as the only IrAE, occurring after her first dose of pembrolizumab, and this led to treatment discontinuation. Four patients were diagnosed with anterior uveitis, one had intermediate uveitis, one had melanoma-associated retinopathy (MAR) 19,20 and one had suspected ocular ischaemic syndrome. 21 All patients had bilateral eye involvement.…”
Section: Resultsmentioning
confidence: 99%
“…Of interest, Keltner et al suggested that the presence of MAR was associated with prolonged survival in 62 melanoma patients [ 8 ]. This has been hypothesized to be mediated by antibodies directed at specific epitopes located on melanoma cancer cell which leads to effective antitumor immunity [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Autoimmune retinopathies (AIR) are rare but devastating autoimmune diseases in humans, characterized by the sudden onset of severe visual deficits (or complete blindness), extinguished retinal electrical activity, relatively normal fundus appearance, and presence of serum retinal autoantibodies 9‐11 . AIRs can develop as a form of paraneoplastic syndrome (ie, CAR: cancer‐associated retinopathy; MAR: melanoma‐associated retinopathy), or in the absence of cancer (nonparaneoplastic autoimmune retinopathies: npAIR) 12‐15 . Patients suffering from npAIR can share features of CAR and MAR; however, it is believed that this retinal disease does not develop as a direct result of a cancer 13 …”
Section: Introductionmentioning
confidence: 99%
“…While there is an extensive body of literature describing the functional and morphological properties of CAR and MAR in humans, 14,27,29‐31 a description of CAR is lacking in the veterinary ophthalmology literature. A single review manuscript describes the features of possible immune‐mediated retinitis (IMR)—CAR in canine patients 2 .…”
Section: Introductionmentioning
confidence: 99%